Corner kick characteristics: a case study of the 2020/21 Northern Ireland Football League (NIFL) premiership season - Goodman, J.; Ferguson, K.; Paradis, K. (International Journal of Performance Analysis in Sport, 2024)
In the 2020/21 NIFL Premiership regular season, 12% (70) of goals scored came from corner kicks. However, the effectiveness of corner kicks at a club level ranged from 5% to 17.5%. Thus, individual coaches ability to create effective strategies to impact corner kick outcomes justifies investigation. The aim of this study was to describe how corner kicks were taken across the 2020/21 (NIFL) Premiership season, and to assess the effectiveness of offensive and defensive corner kick strategies. From 195 matches, 1988 corner kicks from video recordings were analysed, examining 18 corner kick outcome variables. Results were recorded using a hand notation observation instrument and data analysed through Microsoft Excel v16.59 and IBM SPSS v27. 70 goals were scored (3.5% of corners taken), accounting for 12% of goals scored (581). Defending team quality (p = 0.034), venue (p = 0.005), and path of ball (p = 0.002) significantly affected the likelihood of an attempt at goal. Most goals came from inswinging corners (80%) and were most likely (5.4%) to be scored when the ball was delivered into the central area of the 6-yard box (GA2). To better understand individual corner style and contextual factors, further research should focus at team level.